Trend of type 1 diabetes incidence in children between 2009 and 2019 in Elazig, Turkey - Esen, Ihsan; Okdemir, Deniz (Wiley, 2020)
Objective: To assess the incidence of T1D in children aged <15 years in Elazig, Turkey. Method: The data of children who have been registered as child with T1D in the database of pediatric diabetes clinic was analyzed. Childhood census data were acquired from the Turkish Statistical Institute. The incidence rates of T1D were calculated for the whole group as well as separately for age group, gender, year of diagnosis, and place of residence, viz. either urban or rural per 100 000 persons per year. The change of incidence during the 10 year observation period was analyzed. Results: The overall mean incidence of T1D in study period was 16.7/100 000 [95% confidence interval (CI): 14.6-19.0] persons per year. The incidence rates of T1D varied from 10.2 to 24.1/100 000 persons per year, representing 2.4-fold variation between 2009 and 2019. The lowest incidence rate was in children aged 0 to 4 years (9.6/100 000 persons per year; CI: 6.9-12.9). There was no difference in incidence rate between genders, incidence rates was significant higher in urban residents. A significant increasing trend of T1D was detected in the total 10-year observation period; the average annual percent change was 7.8%. Subgroup analysis showed that there was significant increasing trend in boys, urban residents, and children aged 5 to 9 years groups. Conclusion: This study demonstrated increase in T1D incidence of in children in Elazig and highest regional incidence rate of T1D until now in Turkey compared to previous limited data.
Keywords: Adults 0-29 Years; Nationwide Incidence; Childhood; Mellitus; Seasonality; Birth